Teachers' perceptions of online challenges in Junior Secondary Schools teachers in South Sulawesi, Indonesia - Indrawaty Asfah; Muhammad Asfah Rahman; Fitriyani Fitriyani (Center for Humanities and Innovation Studies, 2022)
Since the suspension of all types of face-to-face activities during the pandemic, colleges, secondary schools, and elementary schools have adopted the strategy of online education. As a result, teachers and students have used online teaching and learning on an unprecedented scale. Online learning or e-learning has been assumed to be a significant tool for effectively continuing the teaching-learning process during the lockdown. Teachers and students have had to quickly alter their teaching and learning strategies, regardless of whether they were experienced in and prepared for online education, an environment with electronic devices and online applications. Despite the innumerable potentials and benefits of online learning, such as cost-effectiveness, promoting self-paced learning, better retention, and catering to learners' needs, teachers may not readily make the most and get the full benefits of online learning. Some studies have shown that learning achievement in online learning is lower than in traditional face-to-face learning. The present study explores the teachers' perception of the use of digital technology in their online instruction and challenges or problems they face when implementing online learning instruction. Besides, this study will discuss the teachers' measures to respond to and cope with the problems.